2012 Labour Overview : Latin America and the Caribbean. - Office, International Labour (International Labour Office, 2012)
New labour indicators for Latin America and the Caribbean portray a region that is experiencing its finest moment despite the crisis in other latitudes. The ILO's 2012 Labour Overview for Latin America and the Caribbean reports that the unemployment rate has continued its decline and that real wages, formal employment and social protection coverage have all increased.